2014
DOI: 10.2525/ecb.52.51
|View full text |Cite
|
Sign up to set email alerts
|

Night-break Effect of LED Light with Different Wavelengths on Shoot Elongation of Chrysanthemum morifolium Ramat ^|^lsquo;Jimba^|^rsquo; and ^|^lsquo;Iwa no hakusen^|^rsquo;

Abstract: Chrysanthemum morifolium Ramat 'Jimba' and 'Iwa no hakusen' were used as the plant materials. They flower in September and June under natural conditions in Japan. Shoots that were 10 cm in length were planted in plastic cases (32 cm 43 cm 10 cm) filled with BM2 (Berger Peat Moss Ltd., Canada). Each plastic case was divided

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…The Fr light induced increase of the plant height, irrespective of the order of the two light qualities used ( Figure 1 A). The results are in agreement with those of Liao et al [ 23 ] who suggested the enhancement of shoot extension by Fr light during the photoperiod. Shoot elongation is generally controlled by the endogenous gibberellins.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The Fr light induced increase of the plant height, irrespective of the order of the two light qualities used ( Figure 1 A). The results are in agreement with those of Liao et al [ 23 ] who suggested the enhancement of shoot extension by Fr light during the photoperiod. Shoot elongation is generally controlled by the endogenous gibberellins.…”
Section: Discussionsupporting
confidence: 93%
“…Shoot elongation is generally controlled by the endogenous gibberellins. The Fr light possesses the ability to induce the gibberellin biosynthesis resulting in increased shoot elongation [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, internode elongation is reported to be caused by gibberellin biosynthesis activated by far-red light irradiation (Pierik et al, 2004;Hisamatsu et al, 2005); in general, far-red light promotes plant internode elongation. Furthermore, some reports indicate far-red light in NB and end-of-day treatments affect stem elongation in chrysanthemum (Erik and Royal, 2001;Franklin and Whitelam, 2005;Hirai et al, 2006;Liao et al, 2014b). The present results indicate all cultivars conserved these responses regardless of their flowering types.…”
Section: Effects Of Nb Treatments On Plant Height and Leaf Numbersupporting
confidence: 71%
“…The light quality imposes important effects on the morphogenesis, photosynthesis (Kitazaki et al 2018), and flowering (Liao et al 2014) of plants. The growth and development of plants throughout their life cycles are controlled by photoreceptors; furthermore, photoreceptors monitor the light environment and help time key developmental transitions such as germination and flowering initiation (Kami et al 2010).…”
Section: Introductionmentioning
confidence: 99%